TYPES OF TITLE IN A FICTION TEXT (American Journal of Interdisciplinary Research and Development, 2022)
This article deals with the problem of determining the place of title in a number of other components, as well as its relationship with the literary text. The analysis of this question involves the research of the definition of "title", its types and functions within the literary text.